Pengaruh Profitabilitas, Dividend Payout Ratio, Dan Nilai Perusahaan Terhadap Harga Saham Pada Perusahaan Sektor Financial Pada Tahun 2018-2021 - Frischa Sitohang; Francis Hutabarat; Judith Tagal Gallena Sinaga (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
At the beginning of 2020, COVID-19 was officially declared a pandemic that hit Indonesia and had an impact on the company's revenue and profitability. Operational activities and production were limited, thus threatening the company. However, amidst the issues occurring within the industry, which experienced a decline due to COVID-19, banking profit margins increased in Indonesia. Therefore, the aim of this research is to find out whether share prices are influenced by profitability variables such as return on equity, dividend payout ratio, and company value with price earnings ratio in the financial sector on the Indonesia Stock Exchange in 2018–2021. The population in this case is all publicly traded companies listed on the Indonesia Stock Exchange in 2018–2021, with a sample selection technique using purposive sampling. The method used in this research is to carry out descriptive test analysis, correlation tests, determination tests, F tests, and multiple regression tests with partial results. Share prices are not influenced by profitability as measured by return on equity, and partially, share prices are not influenced by dividend payout ratio. Partially, share prices are not influenced by the price-earning ratio, so profitability, dividend payout ratio, and price-earning ratio do not significantly influence share prices.